Identification of the fetal liver cytochrome CYP3A7 in human endometrium and placenta. - Schuetz, J D (1993)
Placenta and endometrium carry out steroidogenic biotransformation reactions such as 6-beta-hydroxylation of cortisol, a reaction characteristic of the dominant family of cytochromes P450 in human liver, CYP3A. To investigate the possible role in these extrahepatic tissues of the CYP3A microsomal hemoproteins, we analyzed placental and endometrial microsomes on Western blots developed with an anti-human CYP3A antibody. We found an immunoreactive 51,500 D protein that migrated between CYP3A3 (HLp) and CYP3A5 (HLp2) identical with CYP3A7 (HFLa). CYP3A7, a form found prominently in human fetal liver microsomes, was first isolated as a liver 16-alpha-dehydroepiandrosterone-sulfate hydroxylase. Northern blot analysis of total RNA isolated from placenta or from endometrium demonstrated a single band that cross-hybridized with a CYP3A7 cDNA. Amplification of the same RNA samples with the use of primers specific for CYP3A7, produced a 552-bp segment that had the predicted size and the same DNA sequence as does liver CYP3A7 cDNA. Hybridizable endometrial CYP3A7 mRNA was detected more frequently (six of seven samples) and in higher amounts (approximately 12-fold higher) in pregnant compared with nonpregnant women (4 of 12 samples). In addition, during the secretory phase of the menstrual cycle CYP3A7 expression was sixfold higher than in the one sample from the proliferative phase that had detectable CYP3A7 mRNA. Moreover, the amounts of placental and endometrial CYP3A7 mRNA and protein increased substantially from the first to the second trimester of pregnancy. We conclude that placenta and endometrium express the same P450 as is found in fetal liver. These tissues represent a previously unrecognized and quantitatively important site for 6-beta-hydroxylation and 16-alpha-hydroxylation of specific steroid precursors, possibly for protection of the fetus from the toxic effects of endogenous steroids and foreign substrates.